Effectiveness of Contextual Phenomena-Based Learning to Improve Science Literacy - Aprilia Nurhijriyah Santoso; Titin Sunarti; Wasis Wasis (International Journal of Current Educational Research, 2023)
Objective: This study aimed to determine the effectiveness of contextual phenomena-based learning to increase scientific literacy in three Basic Physics materials.. Method: This research method is descriptive and quantitative with the type of Pre-Experimental research. The subjects of this study were 27 students of Physics Education class A at Surabaya State University class of 2022. Result: The results of the data analysis showed that learning based on contextual phenomena to increase scientific literacy was an excellent category to apply. This is shown by implementing learning on the three materials with suitable criteria. Student activities for each material are in very good criteria. Moreover, the average N-gain value obtained through the Pre-test and Post test scores on the third material is in the high category. As well as the results of the average student response to the learning that is applied is also in the high category and gets a positive response from students. From the four results of data analysis, it can be interpreted that learning based on contextual phenomena effectively increases scientific literacy. Novelty: The application of contextual phenomena-based learning in the materials on Works and Energy, Momentum, and Fluids at the college level to improve scientific literacy